Through the Looking Glass: Estimating Effects of Medical Homes for People with Severe Mental Illness. (21st October 2016) - Domino, Marisa Elena; Kilany, Mona; Wells, Rebecca; Morrissey, Joseph P.
Abstract : Objective: To examine whether medical homes have heterogeneous effects in different subpopulations, leveraging the interpretations from a variety of statistical techniques. Data Sources/Study Setting: Secondary claims data from the NC Medicaid program for 2004–2007. The sample included all adults with diagnoses of schizophrenia, bipolar disorder, or major depression who were not dually enrolled in Medicare or in a nursing facility. Study Design: We modeled a number of monthly service use, adherence, and expenditure outcomes using fixed effects, generalized estimating equation with and without inverse probability of treatment weights, and instrumental variables analyses. Data Collection: Data were received from the Carolina Cost and Quality Initiative. Principal Findings: The four estimation techniques consistently revealed generally positive associations between medical homes and access to primary care, specialty mental health care, greater medication adherence, slightly lower emergency room use, and greater expenditures. These findings were consistent across all three major severe mental illness diagnostic groups. Some heterogeneity in effects were noted, especially in preventive screening. Conclusions: Expanding access to primary care–based medical homes for people with severe mental illness may not save money for insurance providers, due to greater access for important outpatient services with little cost offset. Health services research examining more of the treatment heterogeneity may contribute to more realistic projections about medical homes outcomes.